Cognitive Distortions and their Relationship to Symptoms of Obsessive-Compulsive Personality Disorder among Adolescents - Abbara, Hani; Rahal, Mario; haj Mosa, Ahmad (Jordan Journal of Educational Sciences, 2018)
The present study aimed to explore the level of cognitive distortion and symptoms of obsessive-compulsive personality disorder among adolescents, and to know if there is a difference in cognitive distortions and symptoms of obsessive-compulsive personality according to the variables of sex and specification. This study also aimed to investigate the relationship between cognitive distortions and symptoms of obsessive-compulsive personality disorder among adolescents. The sample of the study consisted of (389) students (189 males; 200 females) in some high school students. To achieve the aims of this study, the present researchers designed a scale of cognitive distortions, and a scale of symptoms of obsessive-compulsive personality disorder, then normalized them to high school students. The results of the study showed that the cognitive distortion level was high in general; the symptoms of obsessive-compulsive personality disorder was also high in general. There was no statistically significant difference between males and females on the scale of cognitive distortions as a whole and its subscales except for the subscale of Emotional Logic where there was a difference for females. There was no difference between scientific students and literary students on the scale of cognitive distortions as a whole and its subscales except for the subscale of arbitrary inference and the subscale of over-generalization, where there was a difference for literary students. There was no difference between males and females, and between scientific students and literary students on the scale of symptoms of obsessive-compulsive personality disorder. The study also showed that there was a significant positive relationship between the student grade’s on the scale of cognitive distortions as a whole and its subscales and their grads on the scale of symptoms of obsessive-compulsive personality disorder as a whole and its subscales